Comparative study between Mini open and all arthroscopic rotator cuff full thickness tear repair in Iraqi patients - Lecturer Dr. Hasan AbdulHadi Mohammed (Zien Journals, 2023)
One of the most prevalent shoulder pathologies in both young and older age groups is rotator cuff tears. This paper aims to conduct a comparative study between mini-open and all arthroscopic rotator cuff full-thickness tear repair in Iraqi patients. Patient and methods: This study was a comparative study between mini-open and all arthroscopic rotator cuff full-thickness tear repair in Iraqi patients, with 42 cases were collected from Anbar - Iraq hospitals between 18th March 2021 to 16th April 2022. This study was conducted to divide patients into comparison mini-open surgery with (22) and arthroscopic surgery with (20) for patients above 35 and under 60 years. The comparative study data of rotator cuff patients were analysed by the SPSS program. Results and discussion: In the present study, which is comparing the results for mini-open as well as all-arthroscopic surgeries for RCTR, it was found that patients who underwent arthroscopic surgery experienced less pain in the immediate postoperative period, improved shoulder flexion, and a lower incidence of complications. Numerous studies comparing the results of all-arthroscopic and mini-open procedures have been done in the past literature, and they all found comparable results. Our study examined the complication rates following arthroscopic compared to open rotator cuff surgery. According to the authors, individuals receiving open surgery were more likely to experience any unfavorable side effects and be readmitted following surgery during 30 days of their first procedure. The patients having open surgery remained older and were more probable to have concomitant illnesses, though. Conclusion: According to the study's findings, individuals with rotator cuff tears who underwent arthroscopic surgery experienced less pain than those who underwent small open surgery, had greater shoulder flexibility and function after surgery, and experienced no post-operative complications. Our findings could help to explain why arthroscopic surgery is so common among surgeons
Keywords: Rotator cuff; mini-open surgery; and arthroscopic surgery